2019
DOI: 10.1088/1361-6528/ab484a
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer/magnetic nanoparticles decorated with fluorescent gold nanoclusters for selective detection and collection of human promyelocytic leukemia (HL-60) cells from a mixture

Abstract: In the present work, a fluorescent gold nanoclusters (GNCs)/superparamagnetic (Fe 3 O 4 /GNCs) nanoprobe was prepared via a facile approach for the selective detection and imaging of human leukemica cancer cells (HL-60). (γ-Mercaptopropyl)trimethoxysilane (MPS) was used as a stabilizer to prepare functionalized GNCs. The prepared GNCs@MPS was then self-assembly decorated on the surface of Fe 3 O 4 @SiO 2 nanoparticles followed by poly(ethylene glycol) dimethacrylate (PGD) addition at room temperature to form F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Gold nanoparticles with aptamer have been widely applied in biosensors and imaging but not in brain-targeting delivery carriers. [32][33][34] However, no study has been performed to evaluate the effects of aptamers conjugated with gold nanoparticles to treat glioma. In this report, we tentatively propose that the U2-AuNP complex could effectively cross the blood-brain barrier and accumulate around GBM in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Gold nanoparticles with aptamer have been widely applied in biosensors and imaging but not in brain-targeting delivery carriers. [32][33][34] However, no study has been performed to evaluate the effects of aptamers conjugated with gold nanoparticles to treat glioma. In this report, we tentatively propose that the U2-AuNP complex could effectively cross the blood-brain barrier and accumulate around GBM in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…(1) detection of leukemia or lymphoma cells based on unique antigen-receptor genes of Tand B-cells, (2) detection of genetic mutation(s), (3) identification of chromosomal deletions, translocations, or duplications, and (4) proteomic changes [71][72][73][74]. This section will report the accuracy, specificity, and reliability of aptamer, biocompatible polymer, antibody, nucleic acid, or ligand-tuned GNMs in the diagnosis of HMs.…”
Section: Gold-nanomaterial-based Diagnosismentioning
confidence: 99%
“…Haghighi et al, (2020) [71] reported that gold nanocluster (GNC) modified with Fe3O4 and KH1C12 aptamer selectively diagnosed highly malignant HL-60 human-leukemia cells from a mixture of different cells. This nanoprobe could be used in MRI imaging (T 2 -based) or fluorescent-microscopy-based diagnosis of leukemia cells (as low as 10 cells µL −1 ).…”
Section: Detection Of Cancer Cellsmentioning
confidence: 99%
“…Finally, nanomaterials can be detected in vivo, e.g., in xenografted mice using MRI, nuclear imaging methods (SPECT, PET/CT, autoradiography), NIR fluorescence imaging systems, or photoacoustic imaging. For MRI, it is required for the nanomaterials to include or to be coated with a heavy metal such as iron oxide or gadolinium [72,73]. On the other hand, nuclear imaging methods require the labeling of the nanomaterials with radioisotopes [74].…”
Section: Tumor Biomarker Detection By Metallic Nanomaterialsmentioning
confidence: 99%